Ending the blame culture - Pearn, Michael (Gower, 1998)
This book is about mistakes and what we can learn from them. It faces up to, and explains how organizations can escape from 'blame cultures', where fearful conformance and risk avoidance lead to stagnation, to 'gain cultures' which tolerate and even encourage mistakes in the pursuit of innovation, change and improvement. Ending the Blame Culture was written as a result of systematic analysis of the content of over 200 accounts of real mistakes within businesses and organizations. This analysis provides both insight and understanding into the type of mistakes made, the context they were made in and how they helped learning and development. As a result the authors are able to distinguish between intelligent and undesirable mistakes: those which should be tolerated and those which must be avoided. The result is a book which gives sound advice on how individuals learn, practical measures that organizations can adopt to enhance learning through better management of mistakes, and the promotion of a culture which supports and fosters experimentation and risk taking.